2013
DOI: 10.1515/revac-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric identification and differentiation of botulinum neurotoxins through toxin proteomics

Abstract: Botulinum neurotoxins (BoNTs) cause the disease botulism, which can be lethal if untreated. There are seven known serotypes of BoNT, A-G, defined by their response to antisera. Many serotypes are distinguished into differing subtypes based on amino acid sequence and immunogenic properties, and some subtypes are further differentiated into toxin variants. Toxin characterization is important as different types of BoNT can respond differently to medical countermeasures for botulism, and characterization of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As a potential diagnostic antibody for BoNT/A, it has good specificity and does not exhibit cross reaction with enterotoxins and BoNT/B. It could clearly distinguish between BoNT/A and BoNT/B, which is very important for botulism detection, because different serotypes of botulism need to be neutralized with specific antisera ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a potential diagnostic antibody for BoNT/A, it has good specificity and does not exhibit cross reaction with enterotoxins and BoNT/B. It could clearly distinguish between BoNT/A and BoNT/B, which is very important for botulism detection, because different serotypes of botulism need to be neutralized with specific antisera ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…For antigen-antibody reactions, it has previously been reported that the acidity of freshly squeezed orange juice and the fat or casein in milk can affect antigen-antibody binding, which could negatively affect the assay ( 15 ). To reduce the effects of the food matrix, some studies isolated, tested, and quantified toxins from food samples ( 3 , 16 ). In this study, the AlphaLISA method was not only found to be sensitive and rapid, but also showed a certain tolerance to a variety of different sample type matrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An arsenal of different methods has been developed in the BoNT field which can be roughly grouped into (i) immunological assays detecting the presence of the molecule [34], (ii) in vitro biochemical methods such as Endopep-ELISA and Endopep-MS detecting the catalytic activity and the serotype [35,36], and (iii) the functional in vitro cell-based assay [37], ex vivo mice phrenic nerve (MPN) hemidiaphragm assay [38], and in vivo mouse bioassay (MBA) [34] which measure the full biological activity and toxicity. However, apart from the mouse bioassay [39] and one sandwich ELISA [40], none of the other methods had been evaluated in a PT or method performance study until recently.…”
Section: Bonts From Clostridium Botulinum and Other Clostridia Sppmentioning
confidence: 99%
“…For example, proteomics has been used to characterize items of historical and archeological significance, including ancient paints, , tuberculosis-ridden skeletal remains, and South American ungulates from the last Ice Age . A number of law enforcement applications have been described, including microbial identification, characterization of microbiological growth media, human identification from hair samples, , identification of bodily fluids, species identification using bones and other tissues, as well as detection of protein toxins such ricin, the botulinum neurotoxin, , and others. ,, …”
Section: Introductionmentioning
confidence: 99%